Advertising the 2015 Cricket World Cup: Representing Multicultural Female Sports Fans. (April 2017) - Toffoletti, Kim
Intersectional accounts of how women sports fans from diverse cultural backgrounds are represented remain largely unconsidered in fandom literature. This article examines an Australian advertisement for the 2015 Cricket World Cup, which features as its main protagonists female cricket fans supporting a variety of countries. It makes use of a transnational feminist cultural studies paradigm to frame a discussion of how commercial sports media narratives situate these fans as "ordinary." In considering how the multicultural female sports fan is configured as ordinary in the Australian sporting context, I demonstrate the ways in which narratives of gender and nation are mobilized to situate multicultural women as marginal to both the Australian nation and cricket, despite the prominence given to ethnically diverse women in the advertisement. This manoeuvre, I argue, responds to the cultural and economic transformations of cricket globally, simultaneously denying and universalizing difference as a mechanism to assuage the anxieties generated by the decentering of Western power in international cricket.